Plastic Pipe Crack Detection Using Ultrasonic Guided Wave Method - M. F., Ghazali; Priyandoko, Gigih; Wan Sofian, Wan Hamat; Tan, Wan Ching (2014)
The basic components of a plastic material made it very sensitive to damage, which requires techniques for detecting damage reliable and efficient. Ultrasonic guided wave is a sensitive method for damage detection. It is a method based on propagation of low-frequency excitation in solid structures. Experimental works are performed to investigate the effect of crack to the frequency signal. Ultrasonic guided wave tests are performed for the uncracked and cracked plastic pipes. The study involves the analysis of signal between the uncracked and cracked frequency graph. This paper focuses on the detection of damage by using ultrasonic guided wave method, whose main objective is to determine performance of ultrasonic guided wave method in order to detect crack in pipeline. The frequency signal for an uncracked pipe shows one peak which is the operating frequency by the piezoelectric actuator itself while the frequency signal for single cracked pipe shows two peak which is the operating frequency by the piezoelectric actuator itself and the resultant frequency from the crack. For multi cracked pipe, the frequency signal shows more than two peak depend the number of crack.The experimental results show that this method can enhance the accuracy and precision of pipeline crack detection.